Editorial for the Special Issue on “Quantum-Dot Cellular Automata (QCA) and Low Power Application” - Stefania Perri (Journal of Low Power Electronics and Applications, 2018)
Challenges created by the trend of increasingly reducing the size of transistors have made necessary innovative technologies to limit undesirable impacts on the performance speed and power consumption of future designs. [...]